Use of a Si/CdTe Compton Camera for In vivo Real-Time Monitoring of Annihilation Gamma Rays Generated by Carbon Ion Beam Irradiation - Shiba, Shintaro; Parajuli, Raj Kumar; Sakai, Makoto; Oike, Takahiro; Ohno, Tatsuya; Nakano, Takashi (Frontiers in Oncology, 2020)
The application of annihilation gamma-ray monitoring to the adaptive therapy of carbon ion radiotherapy (C-ion RT) requires identification of the peak intensity position and differentiation of annihilation gamma rays generated at the C-ion-irradiated site from those transported to unirradiated sites. Real-time monitoring of C-ion-induced annihilation gamma rays was effected using a Compton camera in a mouse model. An adult C57BL/6 mouse was anesthetized, and C-ion beams were directed into the abdomen at 1 × 109 particles/s for 20 s. The 511 keV annihilation gamma rays, generated by the interaction between the irradiated C-ion beam and the target mouse, were detected using a silicon/cadmium telluride (Si/CdTe) Compton camera for 20 min immediately after irradiation. The irradiated site and peak intensity position of the gamma-ray emission were visualized by developing Compton images, and the annihilation gamma-ray transport was visualized similarly after the C-ion beam irradiation. These data showed that the gamma-ray transport pattern was wider than the size of the C-ion beams. Our data suggest the applicability of a Si/CdTe-based Compton camera to adaptive therapy using C-ion RT; by identifying the peak intensity and the beam range of C-ion irradiation, this technique can help minimize intra-fractional and inter-fractional dose distribution degradation.